ACTR-65. SAFETY PROFILE OF TUMOR TREATING FIELDS IN ADULT GLIOBLASTOMA PATIENTS WITH IMPLANTED NON-PROGRAMMABLE SHUNTS, PROGRAMMABLE SHUNTS, AND PACEMAKERS/DEFIBRILLATORS: 6-YEAR UPDATED RETROSPECTIVE ANALYSIS OF OPTUNE® THERAPY - Kew, Yvonne (Neuro Oncol, 2017)
BACKGROUND: Tumor Treating Fields (TTFields) are a noninvasive, loco-regional, anti-mitotic cancer treatment approved in the U.S. for adults with recurrent and newly diagnosed glioblastoma (GBM). TTFields (low intensity, intermediate frequency, alternating electric fields) are delivered by a portable medical device (Optune®). GBM patients may develop hydrocephalus and benefit from subsequent shunt placement. Safety information on concomitant use of TTFields with implanted devices in GBM patients will identify potential interference with the functioning of these devices. METHODS: A review of the clinical information for GBM patients treated with TTFields in the U.S. between November 2011 and June 2017 identified 50 patients with non-programmable shunts (NPS), 5 with programmable shunts (PS), and 5 with pacemakers/defibrillators (PM/DF). The safety data obtained from post-market surveillance in all 60 patients were analyzed to identify implantable device-related adverse events. RESULTS: Adverse events (AEs) reported for these 60 patients did not reveal any new safety concerns on concurrent use of Optune with implanted devices. Infections or infestations (bronchitis, diverticulitis, infection NOS, meningitis, sepsis, shunt infection, upper respiratory and urinary tract infections, wound infection) were reported in 7/50 (14%) of NPS patients and in 1/5 (20%) PS patient. No arrhythmia or other cardiac adverse events were reported in the 5 patients with PM/DF. Skin irritations were seen in 8% of NPS patients (including 2% ulcerations). Neurological symptoms (38%), which included convulsions (16%) in the NPS patients were related to the underlying tumor rather than TTFields treatment. Hydrocephalus was seen in 1/50 (2%) NPS and 1/5(20%) PS patient, neither related to shunt malfunction. CONCLUSIONS: No unexpected safety issues were observed in the 60 patients analyzed in this updated report. Further evaluation of the concurrent use of TTFields with programmable shunts and pacemaker/defibrillators should include bench testing of the electronic immunity of these devices to TTFields.